A Survey on the Use and Barriers of Surface Electromyography in Neurorehabilitation - Manca, Andrea; Cereatti, Andrea; Bar-On, Lynn; Botter, Alberto; Della Croce, Ugo; Knaflitz, Marco; Maffiuletti, Nicola A.; Mazzoli, Davide; Merlo, Andrea; Roatta, Silvestro; Turolla, Andrea; Deriu, Franca (Frontiers in Neurology, 2020)
Historical, educational and technical barriers have been reported to limit the use of surface electromyography (sEMG) in clinical neurorehabilitation settings. In an attempt to identify, review, rank and interpret potential factors that may play a role in this scenario, we gathered information on 1) current use of sEMG and its clinical potential; 2) professional figures primarily dealing with sEMG; 3) educational aspects, and 4) possible barriers and reasons for its apparently limited use in neurorehabilitation. To this aim, an online 30-question survey was sent to 52 experts on sEMG from diverse standpoints, backgrounds and countries. Participants were asked to respond to each question on a 5-point Likert scale or by ranking items. A cut-off of 75% agreement was chosen as the consensus threshold. Thirty-five invitees (67%) completed the electronic survey. Consensus was reached for 77% of the proposed questions encompassing current trends in sEMG use in neurorehabilitation, educational, technical, and methodological features as well as its translational utility for clinicians and patients. Data evidenced the clinical utility of sEMG for patient assessment, to define the intervention plan, and to complement/optimize other methods used to quantify muscle and physical function. The aggregate opinion of the interviewed experts confirmed that sEMG is more frequently employed in technical/methodological than clinical research. Moreover, the slow dissemination of research findings and the lack of education on sEMG seem to prevent prompt transfer into practice. The findings of the present survey may contribute to the ongoing debate on the appropriateness and value of sEMG for neurorehabilitation professionals and its potential translation into clinical settings.